(untitled) (Journal of Medicine, 2021)
Contrast enhance CT scan of Abdomen showing a large encysted collection at the left of the abdomen extending from lumbar region to left iliac region pushing the surrounding viscera forward. Collection was due to retro-peritoneal hemorrhage in a Middle aged Lady with COVID-19 who was on therapeutic dose of anticoagulation with Low Molecular Weight Heparin. J MEDICINE JAN 2021; 22 (1) : 84-85